The rotational diffusion of the acetylcholine receptor in Torpeda marmorata membrane fragments studied with a spin-labelled alpha-toxin: importance of the 43 000 protein(s). - Rousselet, A (1982)
The rotational diffusion of the acetylcholine (ACh) receptor in subsynaptic membrane fragments from Torpedo marmorata electric organ was investigated with a spin-labelled alpha-bungarotoxin. A toxin with two spin labels was first synthesized; the conventional electron spin resonance spectrum (e.s.r.) of this toxin bound to the receptor indicated: (1) a complete immobilization of the probes; and (2) a strong spin-spin interaction that was not, or barely, seen in solution. The modification of the degree of spin-spin interaction is taken as an indication of a toxin conformational change accompanying its binding to the ACh-receptor. To avoid spin-spin interaction a single-labelled toxin was made and used to follow the rotational diffusion of the receptor by saturation transfer e.s.r. (ST-e.s.r.). With native membranes a high immobilization of the ACh-receptor was noticed. Reduction of the membranes by dithiothreitol had little effect on this motion. Only extraction of the 43 000 protein(s) by pH 11 treatment was able to enhance the rotational diffusion of the ACh-receptor protein (rotational correlation time by ST-e.s.r. in the 0.5 - 1 X 10(-4) s range) and to allow its lateral diffusion in the plane of the membrane fragments (observed by electron microscopy after freeze-etching or negative staining).